The Effect of Organisational Learning on Small and Medium-Sized Enterprises (SMEs) Performance in Abeokuta, Ogun State, Nigeria: Array - Shodiya, Abideen Olayinka; Ojenike, Joseph Olushola (Acta Universitatis Danubius. Œconomica, 2021)
Organisational learning is vital for firms to gain competitive edge. Still, there is no indication that it is utilised by SMEs in Nigeria to improve efficiency. Hence, the study examined the effect of organisational learning on SMEs' performance to shed more light on this development.The study's population comprised all SME owners operating in Abeokuta North and Abeokuta South local government area. The Cochran's (1977) sample size formula was used to determine the sample size of 384 SMEs selected using purposive sampling technique across the two local government areas. Data were collected with the use of validated copies of structured questionnaires. The Partial Least Squares Structural Equation Modelling was used to analyse the data collected. The study's findings revealed that information acquisition, information interpretation, and organisational memory significantly and positively affected SMEs' performance. The study concluded that organisational learning had a significant positive effect on SMEs' performance. It was recommended that SME owners acquire information internally and externally through training, seminars, and learning from other SMEs; disseminate the acquired information in simple and easy ways among employees; and ensure that crucial information and decisions made are stored so that concerned individuals could have access to them to enhance organisational performance.